Composição da ictiofauna na área de confluência do Rio Tapajós com o Rio Amazonas, município de Santarém, Pará, Brasil. - DANTAS, Nágila Letícia Fernandes (Universidade Federal do Oeste do Pará, 2023)
The study aimed to conduct a survey on the diversity and composition of the ichthyofauna in the lower Tapajós River near its confluence with the Amazon River, in the municipality of Santarém - Pará, during the low-water period. To achieve this, several faunistic and ecological indicators were used. Collections were carried out from October 30th to December 20th, 2014, at seven sampling sites in river, lake, and stream environments. Seven gill nets with a single mesh size were set in each sampling location for 24 hours, inspected every 6 hours, and manual traction trawl nets were operated in coastal areas for approximately 1 hour. In the stream, seine nets were used in a stretch of approximately 50 meters, followed by simple trawl nets. A total of 6,984 individuals belonging to 179 species were captured. The order Characiformes was the most representative. The most abundant species was Hyphessobrycon sp., followed by Anchoviella sp. A considerable number of commercially and ornamental species were found; however, the species accumulation curve indicates potential for discovering or recording species that were not sampled. It is evident that studies like this play a significant role as they provide essential information on the composition and diversity of fish assemblages, enabling effective conservation and management strategies for the protection and preservation of these environments.